1995
DOI: 10.1002/bspy.350010503
|View full text |Cite
|
Sign up to set email alerts
|

Red‐band resonance raman spectroscopy of chlorophyll cofactors in photosynthetic proteins

Abstract: SYNOPSISOnly recently have various methodological approaches been successful in producing Raman spectra of chlorophylls resonantly with their lowest singlet electronic transitions ( Qy bands). The information content of these new approaches and their impact on current research on photosynthetic proteins are discussed. It is shown that resonance methods can contribute very valuable data on the dynamics of the primary photophysical events, while preresonance methods are yielding many new data on the structural b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…Spectra obtained with the two techniques show good general agreement (10,45,46,47); so it is of interest to compare the results of the present work with those from resonance Raman investigations.…”
Section: Discussionmentioning
confidence: 66%
“…Spectra obtained with the two techniques show good general agreement (10,45,46,47); so it is of interest to compare the results of the present work with those from resonance Raman investigations.…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that acquisition of SERR spectra with both red and blue excitation may facilitate complete characterization of the complicated vibrational spectra of these large pigment structures. 3, 4 We present here an application of this method which reveals good sensitivity of the technique to minor structural differences between closely related members of a family of compounds, the chl a allomers (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Resonance Raman (RR) spectroscopy provides a convenient and direct method for probing both the ground- and excited-state properties of chromophores via the characteristics of the RR frequencies and intensities, respectively . To date, RR spectroscopic methods have been used to investigate a variety of photosynthetic pigments, both in isolated form and in protein systems . The majority of these studies have focused on the high-frequency (1000−1750 cm -1 ) region of the spectrum which contains bands due to ring-skeletal and carbonyl stretching vibrations of the macrocycle. These vibrational data have been used to assess the conformation of the (bacterio)chlorophyll rings, the ligation state of the Mg(II) ion, and the extent of hydrogen bonding to the carbonyl substituents on the rings.…”
Section: Introductionmentioning
confidence: 99%